Dumai Port Area Development and Economics Approach - Gaffara, Ghefra Rizkan (Jurnal Tata Kota dan Daerah, 2021)
Ports are part of a complex urban setting as they provide important economic opportunities, such as access to global supply chains.(Economics, 2021). DivergenceFor an archipelago country that can exploit the maritime potential, Indonesia should be utilizing the potential of logistics transportation aspect, in this research context is Port. The distribution of ports in Indonesia is not evenly distributed if seen from Gross Regional Domestic Product (PDRB), in this case is Dumai City which has a port in the Indonesian archipelagic sea lane (ALKI) 1, although it is in strategic location, it is not reflected from Dumai cityÂ  PDRB that can be categorized as lagging compared to other Port cities in Indonesia. To optimize the utilization of existing ports and increase economic growth in Dumai City, PT. Pelindo 1 of Dumai territory plans to develop port capacity by building a special segment of container loading and unloading activities based on the increasingly cheap vessels of containers docked at Dumai Port. To increase the phenomenon that occurs, the research is intended to design the conceptual design of port development by using dynamic system. The aim to the research are how to know cost maintenance, operation-maintenance and revenue at Dumai Port and how to develop this area